Addressing student diversity and integrative learning in an undergraduate medical curriculum - Chipamaunga, Shalote; Prozesky, Detlef (My University, 2019)
Introduction: South African universities are increasingly enrolling students from a variety of educational backgrounds. This brings in diversity in levels of language and learning ability and universities face the challenge of adjusting their curricula to meet the academic needs of the different learners. The objective of this paper is to document the experiences of students and teachers on a course that was introduced to address student diversity and integrative learning in a higher institution of learning. Methods: The course was evaluated through two ways. Firstly, a student feedback questionnaire was administered to 250 students at the end of the first and second semesters during the first two years of introduction of the course. Secondly, students’ reflections were extracted from in-depth interviews and focus group discussions during the 4th and 5th years of implementation of the course. Results: Due to the diversity in entry level learning and language skills, some units of the course were not rated favourably by about 50% of the students who struggled to see the relevance. However, many students’ experiences with the value of the course in enabling integrative learning were positive. Some students reported that they acquired lifelong skills in critical thinking and problem solving. Conclusion: This paper demonstrates that a course that focusses on helping students to integrate learning is invaluable. Further research is required on the types of strategies and how to implement them to meet the varied needs of students from diverse backgrounds.
Keywords: integrative learning; student diversity; undergraduate medical education